2020
DOI: 10.3174/ajnr.a6706
|View full text |Cite
|
Sign up to set email alerts
|

Multishell Diffusion MRI–Based Tractography of the Facial Nerve in Vestibular Schwannoma

Abstract: BACKGROUND AND PURPOSE: Tractography of the facial nerve based on single-shell diffusion MR imaging is thought to be helpful before surgery for resection of vestibular schwannoma. However, this paradigm can be vitiated by the isotropic diffusion of the CSF, the convoluted path of the facial nerve, and its crossing with other bundles. Here we propose a multishell diffusion MR imaging acquisition scheme combined with probabilistic tractography that has the potential to provide a presurgical facial nerve reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Tractography methods are widely used in cranial nerve studies (Behan et al, 2017; Castellaro et al, 2020; He et al, 2021; Hodaie et al, 2010). To find a better method for OCN reconstruction, we compare the performance of three different direction estimation methods including constraint spherical deconvolution (CSD; Behan et al, 2017; Tournier, Calamante, & Connelly, 2012), multi‐shell multi‐tissue constraint spherical deconvolution (MSMT‐CSD), and DTI (Hodaie et al, 2010) to reconstruct the 3D trajectory of OCN.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tractography methods are widely used in cranial nerve studies (Behan et al, 2017; Castellaro et al, 2020; He et al, 2021; Hodaie et al, 2010). To find a better method for OCN reconstruction, we compare the performance of three different direction estimation methods including constraint spherical deconvolution (CSD; Behan et al, 2017; Tournier, Calamante, & Connelly, 2012), multi‐shell multi‐tissue constraint spherical deconvolution (MSMT‐CSD), and DTI (Hodaie et al, 2010) to reconstruct the 3D trajectory of OCN.…”
Section: Methodsmentioning
confidence: 99%
“…To find a better method for OCN reconstruction, we compare the performance of three different direction estimation methods including constraint spherical deconvolution (CSD; Behan et al, 2017; Tournier, Calamante, & Connelly, 2012), multi‐shell multi‐tissue constraint spherical deconvolution (MSMT‐CSD), and DTI (Hodaie et al, 2010) to reconstruct the 3D trajectory of OCN. In contrast to CSD and DTI, MSMT‐CSD is utilized to fit a five‐tissue‐type segmented tissue image by using multiple b ‐values for the multi‐type tissue fiber orientation distribution (FOD; Castellaro et al, 2020; Jeurissen, Tournier, Dhollander, Connelly, & Sijbers, 2014). To describe the complete OCN pathway, we prepare a careful plan for each method, including the seed imaging, ROAs, and parameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Diffusion MRI and tractography currently represent the only way to reconstruct white matter in humans in vivo, providing a non-invasive and feasible method for evaluating the subcortical pathways changes, especially in glioma surgery [ 21 , 22 , 23 ]. In recent years, its use has been gradually spread for preoperative cranial nerve reconstruction in SBM surgery [ 24 , 25 , 26 ]. In the latter clinical setting, probabilistic tractography currently appears to be an emerging and promising tool to predict the position of displaced cranial nerves around skull base lesions [ 24 , 25 ].…”
Section: Modern Surgical Planningmentioning
confidence: 99%
“…In addition, the main challenging limitations in cranial nerves tacking are represented by their small size, intricate anatomical environment sensitive to susceptibility artifacts, and a limited MRI spatial and angular resolution. Nevertheless, recent studies have demonstrated effective tracking for large cranial nerves such as optic nerve, trigeminal nerve, or acoustic-facial bundle, highlighting the potential role of tractography both in a surgical setting and intraoperative strategy [ 25 , 26 ].…”
Section: Modern Surgical Planningmentioning
confidence: 99%